THE MOST EFFECTIVE TECHNIQUES USED BY SHOTOKAN KARATE JUNIOR FEMALE ATHLETES DURING COMPETITION - Ivaškienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research is to analyze the most effective techniques used by shotokan karate junior female athletes during competition. Summing up the analysis of technique actions performed by the members of the team of Lithuanian Shotokan karate junior female athletes (n=10) it can be noticed that: female athletes most frequently performed arm technique actions; Giakucuki was observed during attacks and counterattacks while mawasigeri was observed in leg technique.